Manuscript of risk factors for cancer cervix: an analysis of 1000 cases - Parija, Jita; Mohapatra, Janmejaya; Padhy, Ashok (International Journal of Research in Medical Sciences, 2017)
Background: The global incidence of cervical cancer varies (5 lakhs new cases/year), highest in developing countries with >50% dying. Identification of risk factors is necessary to curb the disease. Methods: In this study 1000 married women, attending A.H. Regional Cancer Centre Gynecological-Oncology OPD, from April 2016- March 2017 were randomly selected and subjected to Pap smear test of cervix and abnormal smears, biopsied. Histopathological report of HSIL/invasive carcinoma had HPV-DNA testing. Factors like menarche, coitarche, age at marriage, parity, contraception, smoking habit and socio-economic status were noted. Results: In our study, HSIL was 4.2% and invasive cancer was 2.8%. Multiparity (>5) showed invasive cancer in 57.1% of cases. Menarche between 11-13 years had invasive cancer in 67.9%. Incidence of invasive carcinoma in women married < 15 years was 42.9%. Barrier contraception showed protective role. In patients below poverty line, 78.6%, showed invasive cancer. Rural women showed a higher incidence of invasive carcinoma (67.9%). About 53.6% of invasive cancers were positive for HPV DNA. Conclusions: Early menarche, early coitarche, early marriage, high parity, use of contraception other than barrier, low socioeconomic status, poor habitat and HPV infection, carried a high risk of developing cervical cancer. None of the patients in the study group smoked. HPV infection was the most important risk factor. Improvement of socioeconomic status, education and cervical cancer screening of the high-risk group can reduce cervical cancer mortality and morbidity significantly.